The generalizability of temporal focus profiles across cultures: A secondary analysis using data from Japan and the United Kingdom. (1st June 2017) - Chishima, Yuta; McKay, Michael T.; Cole, Jon C.
Abstract: Studies examining time perspective have increased exponentially in recent years, driven by advances in measurement sophistication. Additionally the literature about time perspective has seen a move toward person-centered analyses, away from bivariate or correlational analyses. The Temporal Focus Scale is a relatively new measure that assesses cognitive engagement with the past, present and future. This is the first study to examine the viability of person-centered analyses using this scale across cultures, and to assess how temporal focus clusters relate to criterion variables. Participants were school children in Japan and the United Kingdom. Results show that a four cluster solution was best in both countries, with three broadly similar clusters emerging across the two sites. Lower self-esteem in the United Kingdom was associated with being in the Past Focussed cluster, while in Japan, lower self-esteem was associated with being in the No Focus cluster. Highlights: Temporal Focus Clusters were developed in Japanese and UK adolescent data Three of the four clusters were similar in nature Cultural differences emerged in terms of how clusters relate to self-esteem Lower self-esteem in the UK was associated with Past Focus Lower self-esteem in Japan was associated with No Focus